Effect of Palm Polysaccharides on Growth Performance, Feed Digestibility and Carcass Percentage of Broilers - Sundu , B.; Bahry, S.; Hatta, U.; Damry, H.B. (International Journal of Poultry Science, 2018)
Objective: A study was conducted to determine the effect of diets supplemented with several palm polysaccharides on chicken performance, fecal moisture, feed digestibility and carcass percentage. Methodology: A total of 168 unsexed broiler chicks were used in this trial. The broiler chicks were kept for 4 weeks. The broilers were then transferred into metabolism cages for 1 week for digestibility and fecal moisture studies. On day 35, the broilers were sacrificed by cervical dislocation for carcass measurements. The broiler chickens were fed with starter (23% protein and 13.39 MJ of metabolizable energy) and grower (21% protein and 13.39 MJ of metabolizable energy) diets. Feed and water were provided ad libitum. Six different types of diets: Control (C), control+2 ppm avilamycin (C+avi), control+0.05% copra polysaccharide (C+cop), control+0.05% salak polysaccharides (C+salak), control+0.05% sugar palm polysaccharides (C+sug palm) and control+0.05% sago polysaccharides (C+sag) were used. A completely randomized design was used with six treatments and four replicates of 7 birds each. Results: The study indicated that diets supplemented with avilamycin, copra polysaccharides and salak polysaccharides increased body weight gain (p<0.05) compared to the control birds. Feed conversion ratio was improved due to salak polysaccharide supplementation. A decreased fecal moisture was found in birds fed the diet supplemenetd with avilamycin and sago polysaccharides. The addition of avilamycin, copra and salak polysaccharides in the diets increased feed digestibility. Conclusion: Supplemented diet significantly increased the body weight gain, feed conversion ratio, feed digestibility and decreased the fecal moisture.